1999
DOI: 10.1038/sj.bjc.6690801
|View full text |Cite
|
Sign up to set email alerts
|

A high proliferation rate measured by cyclin A predicts a favourable chemotherapy response in soft tissue sarcoma patients

Abstract: A small but not insignificant number of patients experience a prolonged survival after treatment of metastatic soft tissue sarcoma. This must be weighed against the majority of the patients who benefit little from the therapy, but nevertheless experience its side-effects. It would therefore be of utmost importance to be able to screen for those patients who respond to the treatment. Since proliferating cells are more sensitive to chemotherapy than non-proliferative cells, we measured the proliferation rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Patients with CA-expressing tumors had a longer time-to-progression and better response to treatment compared with their counterparts. Similar observations were made in patients diagnosed with soft-tissue sarcoma (30). CA, in conjunction with CDK2, regulates entry into and progression through the S phase and remains active until the beginning of mitosis.…”
Section: Discussionsupporting
confidence: 59%
“…Patients with CA-expressing tumors had a longer time-to-progression and better response to treatment compared with their counterparts. Similar observations were made in patients diagnosed with soft-tissue sarcoma (30). CA, in conjunction with CDK2, regulates entry into and progression through the S phase and remains active until the beginning of mitosis.…”
Section: Discussionsupporting
confidence: 59%
“…In the preoperative setting, most studies have shown that a higher proliferation index is associated to a higher response rate of anthracycline-based chemotherapy, while the results in metastatic breast cancer are less consistent (Sjöström, 2002). There are data also from other malignancies, indicating that a higher proliferation rate correlates to a better chemotherapy response (Joensuu et al, 1994;Hahka-Kemppinen et al, 1997;Huuhtanen et al, 1999). We are aware of no clinical data on cyclin A as a predictive factor for chemotherapy in breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…High cyclin A score predicted a better chemotherapy response and longer progression-free survival in patients with soft tissue sarcoma (Huuhtanen et al, 1999). To our knowledge, there are no studies of cyclin A as a predictive marker for chemotherapy response in metastatic breast cancer.…”
mentioning
confidence: 91%
“…A previous study on soft tissue sarcoma suggested that cyclin A, but not S phase fraction or Ki67, could predict for chemotherapy sensitivity (22). Studies on breast cancer and proliferation markers as predictors for chemotherapy response have suggested that the S phase fraction might predict chemotherapy response, at least in the neoadjuvant setting (23).…”
Section: Discussionmentioning
confidence: 99%